Functional characteristics and subjective disease perception in patients with COVID-19 two months after hospital discharge - Teraž, Kaja; Šimunič, Boštjan; Peskar, Manca; Marusic, Uros; Pišot, Saša; Šlosar, Luka; Gasparini, Malden; Pišot, Rado (Frontiers in Rehabilitation Sciences, 2023)
Although early inpatient and post-hospital rehabilitation is recognized as necessary, not all COVID-19 patients have access to rehabilitation. There are no published reports in the literature that investigate the outcomes of patients who do not receive rehabilitation after COVID-19. Our aim was to evaluate possible improvements in determinate functional and psychological parameters in COVID-19 patients two months after their hospital discharge. On both time points various motor, cognitive, and clinical measurements such as body composition, tensiomyography, blood pressure, spirometry, grip strength test, Timed Up and Go test, gait speed, 30-second chair-stand test, and Montreal Cognitive Assessment, were performed. Additionally, questionnaires such as the SARC-CalF test, Edmonton frail scale, International Physical Activity questionnaire andThe Mediterranean Lifestyle index were conducted to assess lifestyle characteristics. A total of 39 patients (87.2% male; mean age of 59.1 ± 10.3 years), who were hospitalized due to COVID-19 at the Izola General Hospital (IGH), Slovenia between December 2020 and April 2021, were included. Patients were assessed at two time points (T1 and T2): T1 was taken after receiving a negative COVID-19 test and T2 was taken two months after T1. After two months of self-rehabilitation, we have detected a BMI increase (p < .001), fat free mass increase (p < .001), better Edmonton frail scale (p < .001), SARC-CalF score (p = .014) and MoCA score (p = .014). There were no detected changes in lifestyle habits nor in physical performance tests. It is already known that COVID-19 has long-term negative consequences regardless of the stage of the disease. Our findings support the notion that patients cannot fully regain all their functions within a two-month period without receiving structured or supervised rehabilitation. Therefore, it is crucial to offer patients comprehensive and structured rehabilitation that incorporates clinical, cognitive, and motor exercises.